Circulating PIWI-Interacting RNAs piR-5937 and piR-28876 Are Promising Diagnostic Biomarkers of Colon Cancer - Vychytilova-Faltejskova, Petra; Stitkovcova, Karolina; Radova, Lenka; Sachlova, Milana; Kosarova, Zdenka; Slaba, Katerina; Kala, Zdenek; Svoboda, Marek; Kiss, Igor; Vyzula, Rostislav; Cho, William C; Slaby, Ondrej (Cancer epidemiology, biomarkers & prevention, 2018)
Background: The early detection of colon cancer is one of the main prerequisites for successful treatment and mortality reduction. Circulating PIWI-interacting RNAs (piRNA) were recently identified as novel promising biomarkers. The purpose of the study was to assess the profiles of piRNAs in blood serum of colon cancer patients with the aim to identify those with high diagnostic potential.Methods: Blood serum samples from 403 colon cancer patients and 276 healthy donors were included in this 3-phase biomarker study. Large-scale piRNA expression profiling was performed using Illumina small RNA sequencing. The diagnostic potential of selected piRNAs was further validated on independent training and validation sets of samples using RT-qPCR.Results: In total, 31 piRNAs were found to be significantly deregulated in serum of cancer patients compared with healthy donors. Based on the levels of piR-5937 and piR-28876, it was possible to differentiate between cancer patients and healthy donors with high sensitivity and specificity. Moreover, both piRNAs exhibited satisfactory diagnostic performance also in patients with stage I disease and enabled detection of colon cancer with higher sensitivity than currently used biomarkers CEA and CA19-9. Finally, the expression of analyzed piRNAs in blood restored significantly 1 month after the surgical resection.Conclusions: Based on our findings, piRNAs are abundant in human blood serum. Furthermore, their levels in colon cancer have been observed to be significantly deregulated. However, their involvement in carcinogenesis must be further established.Impact: piRNAs could serve as promising noninvasive biomarkers for early detection of colon cancer. Cancer Epidemiol Biomarkers Prev; 27(9); 1019-28. ©2018 AACR.
Keywords: regulace genové exprese u nádorů; Female; ženské pohlaví; Gene Expression Regulation, Neoplastic; nádory tračníku; lidé; malá interferující RNA; studie případů a kontrol; následné studie; prognóza; Colonic Neoplasms; Follow-Up Studies; Male; nádorové biomarkery; Aged; Case-Control Studies; RNA, Small Interfering; Prognosis; Biomarkers, Tumor; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans